ANALISIS PENURUNAN KADAR LOGAM BESI (Fe) & MANGAN (Mn) DENGAN PENGGUNAAN KOAGULAN TERHADAP AIR TAMBANG BATUBARA PT. ADARO INDONESIA - Norvie Yudi Hasma; Muhammad Ruslan; Eko Rini Indrayatie; Noor Arida Fauzana; Ahsan Saputra (Universitas Lambung Mangkurat, 2023)
The purpose of writing this study is to analyze the influence of coagulants to reduce the levels of dissolved metals Iron (Fe) & Manganese (Mn) from coal mine water The place of the study is in the operational area of the PT. Adaro Indonesia in Tabalong and Balangan Regencies, the object of the study of mine water samples was taken at the Settling pond (SP) X inlet located in the Wara mine area. This research was conducted with an experimental method, namely the Jar Test test with an experimental design compiled in a Non-Factorial Group Randomized Design (RAK) consisting of 6 (six) treatments with 3 repetitions. The analysis method carried out to determine the influence of coagulants on the decrease in Fe and Mn metal levels is to use the Anova and Tukey (BNJ) analysis method. The results of this study from all the treatments that have been carried out on coagulants in the study, the coagulants that have the greatest influence in reducing Fe metal levels are the use of coagulant Y with a combination of treatments with an increase in water pH (caustic soda Y) combined with fast and slow stirring (D1) of: 0,002 mg/L, treatment with an increase in water pH (caustic soda Y) combined with rapid stirring (D2) by: The 0,002 mg/L data analysis with the anova and tukey BNJ tests differed from other treatments. The coagulant that has the greatest influence in reducing Mn metal levels is the use of coagulant Y with a combination of treatment with an increase in water pH (caustic soda Y) + auxiliary coagulant Y combined with rapid mixing (F2) of: 2,509 mg/L, treatment with an increase in water pH (caustic soda Y) + auxiliary coagulant Y combined with slow mixing (F3) of: 2,518 mg/L.